Salve sol : powiesc dla mlodziezy - Dolinska, Maria (Lublin : Wydawn. Lubelskie, 1980)
A biographical novel about the youth of Copernicus, the Polish astronomer of the 15th century.
Keywords: Copernicus, Nicolaus, -- 1473-1543. -- Fiction